Intercessory Rote Prayer, Life Longevity and the Mortality of Roman Catholic Bishops: An Exploratory Study - Banasik-Jemielniak, Natalia (Journal of religion and health, 2021)
Based on a computational analysis of a large dataset, this study explores if there is a significant longevity effect of intercessory prayer for a named individual’s well-being, if he receives a very high number of prayers per annum for an extended period. We relied on an observational cohort study, based on data from 1988 to 2018, including 857 Roman Catholic bishops, 500 Catholic priests, and 3038 male academics from six countries. We measured the covariance of the mean length of life, controlled for nationality. It was found that there is a main effect for occupation F(2, 4391) = 4.07, p = 0.017, ηp2 = 0.002, with pairwise comparisons indicating significant differences between the mean life duration of bishops (M = 30,489) and of priests (M = 29,894), but none between the academic teachers (M = 30,147) and either of the other groups. A comparison analysis between bishops from the largest and the smallest dioceses showed no significant difference t(67.31) = 1.61, p = 0.11. The first analysis proved that bishops live longer than priests, but due to a marginal effect size this result should be treated with caution. No difference was found between the mean length of life of bishops from the largest and the smallest dioceses.